Structure Optimization of Chain Plate of Double-pitch Silent Chain for Conveyor - Tian Hui; Wang Wencheng; Zhao Haixian; Fu Xintao; Wang Feng; Liu Chunzhe (Jixie chuandong)
The chain plate structure of double pitch silent conveyor chain is the variation structural of internal and external composite engaged standard silent chain. The chain cannot normally internal and external composite engage with sprocket because there is no specific numerical relationship of protrusion length,one of the design parameters of silent chain structure,in the meshing principle of silent chain. A parametric model of the chain plate and a simplified model of motion analysis of double-pitch silent conveyor chain drive system are created by Solidworks/Motion software. In order to realize the composite engagement mechanism and the minimum meshing impact force,the height Y of protrusion length and the value δ of protrusion length are defined as variable,and the simulation analysis is carried out. The results show that protrusion length is important influencing factor for realizing internal and external composite engage process of double-pitch silent chain drive system. By the general comparison,the optimal construct parameters are obtained. When the sprocket tooth number is 38,the height Y of protrusion length is 0. 25 PS,and the value δ of protrusion length is 0. 013 PS,the internal and external composite engage process of chain can be realized,and the meshing impact force is smallest and structural is optimum at that time.